Kinetics of 4-Nitrophenol Reduction with Black Tea Extract Conjugated Silver Nanoparticle Catalyst - Rokiy Alfanaar; Yuyun Yuniati; Devi Natalia; Rasidah Rasidah; Lilis Rosmainar; Pandu Gizta Rapi Paksi; Mulani Jeni Lestari Tampubolon (CHEMICA: Jurnal Teknik Kimia, 2023)
The 4-nitrophenol reduction process is one of the slow methods. One way to increase the rate of 4-nitrophenol reduction reactions is to use a catalyst. In this study, the catalyst used was silver nanoparticles conjugated by black tea extract. The stages that have been carried out in research are the synthesis of conjugated silver nanoparticles of black tea extract, the determination of the kinetic profile of 4-nitrophenol reduction, and the study of the influence of inorganic anions on the reduction of 4-nitrophenol with the presence of silver nanoparticle catalysts. The presence of conjugated silver nanoparticles of black tea extract has been shown to increase the kinetics of the degradation reaction of 4-nitrophenol compounds to 85 times compared to without nanoparticles, by changing the value of the reaction rate constant from 0.00006 to 0.0051. The presence of inorganic anions provides information on the decrease in the rate of reduction reactions of 4-nitrophenol.